DDT: Scientists, Citizens, and Public Policy - Thomas R. Dunlap (Princeton University Press, 2014)
EVEN THOSE who vividly remember World War II probably retain only fragmentary memories of the introduction of DDT, despite the wide publicity over the chemical. First used on a large scale in the Naples typhus epidemic of 1943—1944 and during the rest of the war to protect millions of soldiers and civilians against insect-borne diseases, it came home in 1945 on a wave of publicity and high hopes. It was the atomic bomb of insecticides, the killer of killers, the harbinger of a new age in insect control. Scientists predicted better and cheaper control of agricultural pests, the eradication of imported insects—even, some thought, the end of insect-borne diseases. A few towns used DDT during polio scares.1 Still, in 1945 technical marvels were part of daily life, and during the postwar years DDT faded from public notice. Although within a few years production of the chemical was far above that of any of the earlier insecticides, few Americans paid any attention. They saw fruits and vegetables with less insect damage, but perhaps the only time they thought of DDT was when they noticed the neighborhood spray truck going its rounds in the summer. By the late 1950s some scientists and citizens had become concerned about the deaths of birds from concentrated sprays used against the insect vector of Dutch elm disease, but most Americans ignored DDT until 1962, when Rachel Carson's Silent Spring appeared. The book touched off a heated debate, for Carson, dissenting from the common view that DDT and similar compounds were harmless, vigorously attacked both the chemicals and the experts who recommended them. "It is not my contention," she wrote, "that chemical insecticides must never be used. I do contend that we have put poisonous and biologically potent chemicals indiscriminately into the hands of persons largely or wholly ignorant of their potentials for harm"2 The economic entomologists who recommended the chemicals, the companies that made them, and other people—some scientists, some not—leaped to defend DDT and to condemn Carson as a crank. DDT became a political issue, as President Kennedy asked his scientific advisors for a report and Congress held hearings on federal regulation of pesticides. Although there was no immediate change in pesticide policy, Silent Spring permanently changed the climate in which the policy would be made. Pesticides were now a public issue and, through the 1960s at least, public concern over the environment would continue to increase.